Smooth muscle hamartoma/Mastocytoma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2021)
Smooth muscle hamartoma (SMH) is difficult to diagnose due to the variability of size, shape and color. When it has a brownish color and hypertrichosis is not very visible, it can simulate mastocytoma also because at palpation it can become more prominent and evident (pseudo Darier).